Counter-carceral acoustemologies: Sound, permeability and feminist protest at the prison boundary - Russell, Emma K. (Theoretical criminology, 2020)
This article provides an analysis of sonic protest strategies used by anti-carceral feminist coalitions in Melbourne, Australia. Our research demonstrates that sound is a particularly powerful boundary-crosser that can challenge the exclusionary spatial ordering of the prison. Under certain political and geographical conditions, the carceral soundscape, which increasingly restricts ‘who gets to hear what’, can be temporarily breached, altered and re-made by protest noise, rhythm and music, and radio technology. Counter-carceral acoustemologies create alternative ‘soundtracks’ of resistance that both reveal and momentarily displace carceral-spatial control, re-patterning the aural environment of the prison. Such breaches can be countered, however, by various modes of boundary fortification over time. We propose that a more nuanced understanding of carceral space and soundscapes—as relational and in flux—provides greater opportunities for denaturalizing the prison and challenging its seeming permanence in our political and cultural landscapes.